Analysis Of the Effect of Motivation and Work Ethic on Performance Employees with Organizational Commitment as A Variable Intervening at PT. Bariel Indo Global - Koesoema, Yohny; B, Mesra (Lafadz Jaya Publisher, 2023)
This research is to see the influence of Motivation and Work Ethic on Employee Performance with Organizational Commitment as an Intervening Variable. This research uses a quantitative type of research, this research was conducted at the company PT. Bariel Indo Global on Jalan Pergudangan Semanan Megah KAV 21 Daan Mogot KM 18 Jakarta 11850. The population of this study was 60 employees and the sample used was all employees in the company using a saturated sampling technique, data collection was carried out by distributing questionnaires. The research model used is method analysis. The results of this research are that motivation has a positive and insignificant effect on organizational commitment. Work Ethic has a positive and significant effect on Organizational Commitment. Motivation has an insignificant positive effect on employee performance. Work Ethic has a positive and insignificant effect on Employee Performance. Organizational Commitment has a positive and significant indirect influence on Motivation on Performance through Organizational Commitment. The indirect influence of Work Ethic on Performance through Organizational Commitment.